MORPHOLOGY CHARACTERISTICS OF PANICLES AND FLOWER TWELVE GENOTYPES LOCAL RICE OF KUANTAN SINGINGI - Anton Kurniawan; Elfi Indrawanis; Chairil Ezward (Jurnal AGROSAINS dan TEKNOLOGI, 2020)
Germplasm is a very useful genetic resource for assembling a variety. The preservation of germplasm accompanied by characterization is an effort to provide useful genes. The aims of the research is to identify and characterize 12 genotypes local rice in Kuantan Singingi. This research was used purposive random sampling method. Data were collected by identifying the characteristics of 12 genotypes local rice in Kuantan Singingi directly into the field. Data observations were carried out on samples based on the guidelines for the characterization and evaluation system for rice plants, the National Commission for Germplasm (2003) and Bioversity International, IRRI and WARDA (2007). The characters observed were qualitative and quantitative characters on panicle and flower organs. Observation data were processed using Ms. software. Excel and (NTSYS-pc) version 2.02. The results showed that the diversity of the morphological characters of flowers and panicles, where in the 75% similarity coefficient there are 2 groups, namely group I (PL01 with PL05) and group II (PL03 with PL11).